Interactions between health and farm-labor productivity - Asenso-Okyere, Kwadwo; Chiang, Catherine; Thangata, Paul; Andam, Kwaw S. (International Food Policy Research Institute, 2011)
In the 21st century, agriculture remains fundamental to economic growth, poverty alleviation, improvement in rural livelihood, and environmental sustainability (World Bank 2007). Three-quarters of the world's poor live in rural areas, particularly in Asia and Africa (Ravallion, Chen, and Sangraula 2007), and depend on agriculture as their primary source of livelihood. This report provides an overview of current knowledge of the impact of health issues on farm-level productivity and decisionmaking, and the impact of agriculture on health. Findings are based on a review of the relevant studies of agricultural regions throughout the developing world. Two conceptual frameworks are used to frame this research: (1) Examining the two-way linkages between agriculture and health (2) Tracking the pathway from a disease condition to its effects, including impacts on household decisionmaking and ultimate impacts on livelihood. Agriculture underpins the health of rural households. It provides income that makes households resilient to health shocks; it provides food to meet their nutrient and energy needs; and it provides medicinal plants for treating ailments. But agricultural systems can also have negative effects on health. Agricultural development may lead to environmental change with adverse health impacts: for example, irrigation dams that create suitable conditions for mosquitoes may lead to increased incidence of malaria locally. The use of agricultural inputs such as pesticides by untrained farm personnel often causes illness. Improper food harvesting and storage practices allow mycotoxins to flourish. Lack of diet diversity can lead to malnutrition. Certain animal diseases also can infect humans. Labor migration (including agricultural labor migration) can contribute to high incidence of HIV infection. The effects of ill health on farm households include three broad impacts: absenteeism from work due to morbidity (and eventual death); family time diverted to caring for the sick; and loss of savings and assets in dealing with disease and its consequences. The long-term impacts of ill health include loss of farming knowledge, reduction of land under cultivation, planting of less labor-intensive crops, reduction of variety of crops planted, and reduction of livestock. The ultimate impact of ill health is a decline in household income and possible food insecurity—that is, a severe deterioration in household livelihood. The research found that the household's ability to cope with a shock reflected both its asset portfolio—including human, physical, and financial assets—and its intangible social resources. Good health must be seen as both an investment and consumption asset, like agricultural production, in that it has compounding returns. Health problems, conversely, may trigger a cycle of lowered agricultural productivity and poor health. At the household level, the investment in health can improve resilience and enhance the ability to cope with emergencies, including ill health. But an investment in health in turn requires an adequate livelihood. Access to appropriate inputs (knowledge, land, tools, fertilizer, and seeds) and remunerative markets is necessary to improve the productivity, health, and resilience of farm households.